2015
DOI: 10.4141/cjas-2014-114
|View full text |Cite
|
Sign up to set email alerts
|

Meat composition and quality of young growing Belgian Blue bulls offered a fattening diet with selenium enriched cereals

Abstract: and quality of young growing Belgian Blue bulls offered a fattening diet with selenium enriched cereals. Can. J. Anim. Sci. 95: 465Á473. The objective of this study was to evaluate the effects of selenium (Se) enrichment of cereals on the performance of Belgian Blue bulls, meat quality and chemical composition. Twenty-three bulls were used in the present study. Twelve bulls were offered a control diet containing Se at a basal concentration of 58 mg kg(1 of dry matter (DM) and the other 11 bulls were given a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 47 publications
(67 reference statements)
3
20
0
2
Order By: Relevance
“…The colour characteristics of meat were not altered by supplementation with different selenium levels and sources, a result that agrees with the lack of effect also in the pH value. Similar results were also reported with Se-enrichment diet on meat colour of bulls Mehdi et al, 2015). Shear force ranged from 45 to 52 N and was not influenced (P> 0.05) by selenium levels and sources.…”
Section: Iii43 Meat Qualitysupporting
confidence: 87%
See 3 more Smart Citations
“…The colour characteristics of meat were not altered by supplementation with different selenium levels and sources, a result that agrees with the lack of effect also in the pH value. Similar results were also reported with Se-enrichment diet on meat colour of bulls Mehdi et al, 2015). Shear force ranged from 45 to 52 N and was not influenced (P> 0.05) by selenium levels and sources.…”
Section: Iii43 Meat Qualitysupporting
confidence: 87%
“…Neither level of Se supplementation or source influenced color (L*, a*, b*) data in the current study. In line with these results, Mehdi et al (2015) reported that Se enrichment in cereal not influenced (P>0.05) the color of Belgian Blue meat under retail display conditions. Similarly, Vignola et al (2009) reported no effect of Se source in lamb meat color during 9 days of retail display and Skřivanová, Marounek, De Smet, & Raes (2007) adding Se-enriched yeast in the diet of calves, also not observed influence in meat color.…”
Section: 2 Retail Displaysupporting
confidence: 76%
See 2 more Smart Citations
“…Generally, an increase in the concentration of selenium in the diet results in an increase of the selenium concentration in the serum within 2-6 days after intake [62,63]. Selenium supplementation in diets usually results in an increase of the selenium content and GSH-Px activity in the blood of calves [64], heifers [65] and fattening bulls [66]. Such positive effects become more pronounced when Se is supplemented in organic form as compared to inorganic form [65,67].…”
Section: Assessment Of Selenium Nutritional Status In Animalsmentioning
confidence: 99%